Scrophularia vernalis: a new species record for Turkey, and its comparison with S. chrysantha (Scrophulariaceae) - Uzunhi̇sarcikli Mehmet Erkan; Doğan Güner, Ebru; Özbek, Funda; Eki̇ci̇ Murat (Phytotaxa, 2019)
Scrophularia vernalis (Scrophulariaceae) is recorded from Artvin province (NE of Turkey), which constitutes its first record for the Turkish flora. In this study, an expanded morphological description, geographical distribution, habitat characteristics and ecological features of the species are shown with illustrative figures. Moreover, the pollen and seed morphological characteristics of S. vernalis are determined for the first time and compared with the closely related species S. chrysantha. With this species, the total number of the Scrophularia taxa in Turkey is now 77.